Intracranial myxoid angiomatoid fibrous histiocytoma with "classic" histology and EWSR1:CREM fusion providing insight for reconciliation with intracranial myxoid mesenchymal tumors. Issue 4 (12th July 2021) - Tan, Nicholas J.H.; Pratiseyo, Patricia Diana; Wahjoepramono, Eka J.; Kuick, Chik Hong; Goh, Jian Yuan; Chang, Kenneth T.E.; Tan, Char Loo
Abstract : Angiomatoid fibrous histiocytoma (AFH) is an uncommon soft tissue neoplasm that can exhibit diverse morphological features, including myxoid change. Rarely, the tumor occurs intracranially and poses considerable diagnostic challenges to neuropathologists. This is compounded by a recently coined entity, referred to as intracranial myxoid mesenchymal tumor (IMMT). These tumors show significant overlaps with intracranial myxoid AFH from clinicopathological and molecular genetic viewpoints. We described an unusual intracranial tumor in a 30‐year‐old man. The tumor exhibited "classic" histological features of myxoid AFH and EWSR1:CREM fusion, a relatively novel variant of EWSR1:CREB family fusion, first identified in IMMT. We also performed a comprehensive literature review comparing the clinicopathological features of intracranial AFHs and IMMTs. Peritumoral lymphoplasmacytic cuffing appears to be the only morphological finding that is consistently absent in reported cases of IMMT while being present in most intracranial AFHs. Otherwise, both tumors showed considerable overlaps in clinical, histological, and immunohistochemical features and have a common molecular genetic signature of EWSR1:CREB family fusion, including EWSR1:CREM fusion. Our case appeared to be the first described EWSR1:CREM ‐fused intracranial tumor to show prominent peritumoral lymphoplasmacytic cuffing and myxoid change in addition to most of the other "classic" morphologic features of AFH. As such, while the current literature appears to be lacking when it comes to defining intracranial myxoid AFH and IMMT as separate nosological entities, they likely represent a morphological spectrum of a common entity characterized by EWSR1 rearrangement, akin to solitary fibrous tumors and hemangiopericytomas with the signal transducer and activator of transcription 6 gene ( STAT6 ) rearrangement.